Increased Beat-to-Beat Blood Pressure Variability Is Associated With Impaired Cognitive Function - Nur Fazidah, Asmuje; Sumaiyah, Mat; Choon, Hian Goh; Myint, Phyo Kyaw; Tan, Maw Pin * (Oxford University Press, 2022)
Background: Emerging evidence has linked visit-to-visit, day-to-day and 24-h ABPM blood pressure variability (BPV) with cognitive impairment. Few studies have, however, considered beat-to-beat BPV. This study, therefore, evaluated the relationship between beat-to-beat BPV and cognitive function among community-dwellers aged 55 years and over.